The Myth of Influence of Social Media in the 2024 Presidential Election: Insight from Indonesian Voters in India and Turkiye - Harahap, Raegen; Mujiburrahman (Dirasat: Human and Social Sciences, 2025)
Objectives: This study examines the influence of social media on the electoral decisions of Indonesian voters residing in India and Turkey during the 2024 presidential elections. Despite the prevalence of platforms such as Facebook, Instagram, Twitter/X, YouTube, and WhatsApp as primary sources of political information, the findings reveal a complex and nuanced impact. Methods: A mixed-methods approach was employed, surveying 87 respondents—university students, homemakers, and professionals—via Google Forms distributed through WhatsApp groups. Data collection spanned March to April 2024 in India and October 2024 in Turkey. Semi-structured Zoom interviews provided deeper insights into political preferences and emotional connections to presidential candidates. Results were cross-referenced with credible sources, including academic journals, to align with national trends. Result: The survey revealed that 81.6% of respondents believed social media did not influence their voting decisions, while 17.2% felt it did. Students, the most active social media users, maintained stable political preferences, often citing dissatisfaction with Indonesia's political landscape over the past decade. Homemakers emerged as the most influenced group, whereas professionals expressed skepticism toward social media content, preferring trusted sources. The study highlights the multifaceted nature of media influence, shaped by educational background, professional status, and political experience, offering a comprehensive understanding of the factors driving voter behavior in a global context. Conclusion: The findings challenge the presumed omnipotence of social media in shaping political outcomes, emphasizing the need for a more nuanced evaluation of its influence on electoral decisions.